ANALYSIS OF THE INFLUENCE OF SERVICE QUALITY ON SERVICE CUSTOMER SATISFACTION AT KOODA EASY YOU IN LHOKSEUMAWE CITY - T. Edyansyah; Rico Nur Ilham; Muhammad Roni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
The aim of this research is to identify and analyze the influence of service quality on service customer satisfaction at Kooda Easy You in Lhokseumawe City and to determine the influence of the most dominant dimensions on service customer satisfaction at Kooda Easy You in Lhokseumawe City. The object of this research is consumers who use Kooda Easy You services in Lhokseumawe City. A total of 108 respondents were sampled in this research by interviewing and distributing questionnaires. This research uses Purposive Sampling technique with multiple linear regression analysis, the results of this research show that partially the variables Physical Evidence, Reliability, Responsiveness, Guarantee and Empathy have an rtable value of 0.1874 and an alpha value of 0.05 or 53% and the rest 47% is influenced by other factors outside this research model (error term). From the partial test results, the five independent variables, namely physical evidence (x1) has a value of tcount (1.714) > ttable (1.659), reliability (x2) has a value of tcount (3.104) > ttable (1.659), responsiveness (x3) has a value tcount (0.996) < ttable (1.659), guarantee (x4) has a value of tcount (0.195) < ttable (1.659) and empathy (x5) has a value of tcount (3.058) > ttable (1.659) and the simultaneous test results have an fcount value of (17,894) > Ftable (2,3017). The test results for the coefficient of determination (R2) were 0.465 or 46%, meaning that the service quality variable was 46% due to customer satisfaction, while the remaining 54% was explained by other variables not examined in this research.